Anti-parasitic activities of allium sativum and allium cepa against trypanosoma b. brucei and leishmania tarentolae - Krstin, Sonja; Sobeh, Mansour; Braun, Markus S.; Wink, Michael (Medicines, 2018)
Background: Garlics and onions have been used for the treatment of diseases caused by parasites and microbes since ancient times. Trypanosomiasis and leishmaniasis are a concern in many areas of the world, especially in poor countries. Methods: Trypanosoma brucei brucei and Leishmania tarentolae were used to investigate the anti-parasitic effects of dichloromethane extracts of Allium sativum (garlic) and Allium cepa (onion) bulbs. As a confirmation of known antimicrobial activities, they were studied against a selection of G-negative, G-positive bacteria and two fungi. Chemical analyses were performed using high-performance liquid chromatography (HPLC) and electrospray ionization-mass spectrometry (LC-ESI-MS/MS). Results: Chemical analyses confirmed the abundance of several sulfur secondary metabolites in garlic and one (zwiebelane) in the onion extract. Both extracts killed both types of parasites efficiently and inhibited the Trypanosoma brucei trypanothione reductase irreversibly. In addition, garlic extract decreased the mitochondrial membrane potential in trypanosomes. Garlic killed the fungi C. albicans and C. parapsilosis more effectively than the positive control. The combinations of garlic and onion with common trypanocidal and leishmanicidal drugs resulted in a synergistic or additive effect in 50% of cases. Conclusion: The mechanism for biological activity of garlic and onion appears to be related to the amount and the profile of sulfur-containing compounds. It is most likely that vital substances inside the parasitic cell, like trypanothione reductase, are inhibited through disulfide bond formation between SH groups of vital redox compounds and sulfur-containing secondary metabolites.
Gesehen am 30.10.2019